2009
DOI: 10.1021/cg801069t
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization at Multiple Sites inside Particles of Amorphous Calcium Phosphate

Abstract: Calcium phosphates are the main minerals in human bone, enamel, atherosclerosis, and dental calculus. Amorphous precursors may play a key role in biomineralization. We studied the formation and transformation of calcium phosphate particles of amorphous phase by stopped-flow spectrophotometry, simultaneous measurements of particle size and solution pH, and high-resolution transmission electron microscopy. Ion pairs and clusters formed in the first few seconds. They then constituted initial amorphous phase conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
97
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 22 publications
9
97
2
1
Order By: Relevance
“…The transformation proceeds via direct conversion of an amorphous structure into crystalline ones. This kinetics is attributed to a common cluster unit present in both the amorphous and crystalline phases [11][12][13][14][15]. Posner's cluster [11] and its symmetric isomers [16] were proposed for this common cluster, and then more complex structures of clusters were found through experimental and computational investigations [17,18].…”
mentioning
confidence: 94%
“…The transformation proceeds via direct conversion of an amorphous structure into crystalline ones. This kinetics is attributed to a common cluster unit present in both the amorphous and crystalline phases [11][12][13][14][15]. Posner's cluster [11] and its symmetric isomers [16] were proposed for this common cluster, and then more complex structures of clusters were found through experimental and computational investigations [17,18].…”
mentioning
confidence: 94%
“…Under laboratory conditions, some researchers have suggested that Ca PO 4 precursors crystallize prior to hydroxyapatite formation (Feenstra and de Bruyn 1979), while others have found rapid formation (~85 minutes) of hydroxyapatite (Wang et al 2009). However, given the background P concentration in L22A Haggard et al (2001b) and Marti et al (2004) who studied wastewater treatment water discharge into streams and found SRP uptake lengths of 9 to 31 km (5.6 to 19.3 mi) and 0.1 to 14 km (0.06 to 8.7 mi), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Under laboratory conditions, some researchers have suggested that Ca PO 4 precursors crystallize prior to hydroxyapatite formation (Feenstra and de Bruyn 1979), while others have found rapid formation (~85 minutes) of hydroxyapatite (Wang et al 2009). However, given the background P concentration in L22A , and the thermodynamic data found in PHREEQC, it is unlikely that background water P concentrations were controlled by bottom sediment Ca mineral species because PHREEQC predicted a P concentration of 1.104 × 10 -6 mg L -1 (1.104 × 10 -6 ppm) for the preinjection model.…”
Section: Resultsmentioning
confidence: 99%
“…15 We find that select precursors yield stable amorphous calcium phosphate from electrochemically assisted syntheses, but only in the absence of collagen. Figure 2 shows representative IR spectra that demonstrate collagen's influence on phase selectivity.…”
mentioning
confidence: 82%
“…Our experiments do not substantiate a probable mechanism, but recent theoretical and experimental investigations have begun to address aspects of this question. 6,12,14,15,19 In conclusion, electrochemically assisted synthesis, based on isoelectric focusing, offers an expedient way to make robust collagen-calcium phosphate composites with controlled mineral phase.…”
mentioning
confidence: 98%